A Study of Yeats' Critical Views in His Plays: Exploring the Relationship between Poetry and Drama in Yeats' Works (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Eliot's poetry is dramatic and his drama poetic. His appreciation of the Elizabethan dramatists including Shakespeare is because they are as good dramatists as they are poets. Eliot in the essay ' A Dialogue on Dramatic Poetry' compares a poetic drama to a ballet, to a Christian Mass. Both are the forms of dance, an act in which the dancer cannot the separated from dance. In another essay ' Poetry Drama', Eliot wonders how constantly he has returned to drama, whether by examining the work of the contemporaries of Shakespeare, or by reflecting on the possibilities of the future. As a result, Eliot's thinking on the subject has been constantly modified and renewed by increasing experience. It was perhaps his life-time mission to restore drama to the place it deserved in literature. Eliot's main concern has been to examine whether and if so, why poetic drama has anything potentially to offer the playgoer, that prose drama cannot. He did not view the problem of poetic drama as a kind of conjoining the two genres.